KESIAPAN GURU PENDIDIKAN AGAMA ISLAM DALAM TAHAP IMPLEMENTASI KURIKULUM MERDEKA BELAJAR SEKOLAH DASAR ISLAM TERPADU TAHFIDZUL QURAN - Muhammad Saddang (STAIN MAJENE, 2024)
This research explains the readiness of Islamic Religious Education teachers in each stage of the implementation of the Merdeka Belajar Curriculum at Sekolah Dasar Islam Terpadu (SD IT) Tahfidzul Qur'an in Majene Regency. The purpose of this study is to understand the categories of each stage, namely the initial stage, the developing stage, the ready stage, and the advanced stage of Islamic Religious Education teacher readiness. The type of research used is qualitative to study and understand social phenomena, individual or group behavior, and natural conditions. The data in this study were obtained through data collection through three techniques, namely interviews, observation, and documentation. The results showed that the readiness of Islamic Religious Education teachers at the implementation stage of the Merdeka Belajar Curriculum at SD IT Tahfidzul Qur'an was divided into four stages, namely the initial stage, namely the teacher using an example prepared by the government. At the developing stage, the teacher adjusts to the examples provided by the government. At the ready stage, the teacher makes changes to the examples provided by the government. At the advanced stage, teachers develop by adjusting the needs of schools and students.